1993
DOI: 10.1073/pnas.90.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic metabolism of dietary arginine in relation to nitric oxide synthesis in normal adult man.

Abstract: Urinary nitrate (NO3) is the stable end product of nitric oxide, which is formed, in turn, from a guanidino nitrogen of arginine. We have conducted two experiments, each in four healthy adult men receiving a low nitrate diet for 7-10 days, to investigate the in vivo conversion of arginine to nitrate.In the first study [guanidino-'5N2, 5,5-2H2]arginine was given on day 7 via a primed continuous intravenous infusion for 8 h. In the second study, the labeled arginine was given for 8 h by the intragastric route on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 37 publications
(26 reference statements)
3
83
0
Order By: Relevance
“…This study supports the finding of Castillo et al (3), who showed that NO synthesis represents only 1.2% of the flux of plasma arginine in adults. The fraction of NO synthesis from arginine agrees also in terms of daily amino acid intake; the same group given 28 mmol arginine per day, a figure similar to our estimated intake, found a fractional conversion of labeled arginine to nitrates of 1.95% (18). They found that the contribution of arginine to NO based on intravenous [ 15 N]arginine infusion is lower than that obtained with intragastric infusion (18).…”
Section: Diabetes and L-arginine-no Kineticssupporting
confidence: 54%
“…This study supports the finding of Castillo et al (3), who showed that NO synthesis represents only 1.2% of the flux of plasma arginine in adults. The fraction of NO synthesis from arginine agrees also in terms of daily amino acid intake; the same group given 28 mmol arginine per day, a figure similar to our estimated intake, found a fractional conversion of labeled arginine to nitrates of 1.95% (18). They found that the contribution of arginine to NO based on intravenous [ 15 N]arginine infusion is lower than that obtained with intragastric infusion (18).…”
Section: Diabetes and L-arginine-no Kineticssupporting
confidence: 54%
“…However, while oral L-arginine supplementation can increase circulating [L-arginine] [4,5], and therefore one of the substrates for nitric oxide synthase, whether oral Larginine supplementation increases nitric oxide biomarkers (nitrate and nitrite) and improves exercise performance is controversial [4,[6][7][8][9], see 10 for review]. These conflicting findings might be linked, at least in part, to significant pre-systemic [11,12] and systemic [11,[13][14][15][16] breakdown of orally ingested L-arginine.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for this combination effect might be due to the inhibiting effect of L-citrulline on arginase, which metabolizes L-arginine to urea and L-ornithine. Orally ingested L-arginine is strongly trapped in the gastrointestinal tract and the hepatic tissue, where it is extensively catabolized by arginase, [9][10][11]15) leading to very limited oral bioavailability.…”
mentioning
confidence: 99%
“…8) However, relatively large doses of Larginine are required to produce these effects in humans. Approximately 40% of oral L-arginine is metabolized by arginase on the first pass, 9,10) and a further 15% of systemic L-arginine is abstracted and metabolized by the liver. 11) L-Citrulline is present in the body and is a potent endogenous precursor of L-arginine as part of the recycling system within the L-citrulline-NO cycle.…”
mentioning
confidence: 99%